Science Teacher's Professionalism In Planning Practical Learning Activities - Wiwit Lestari; Hertien Koosbandiah Surtikanti; Taufik Rahman (Syntax Literate, 2023)
Learning is a process of interaction between students and educators and learning resources in a learning environment. Teachers should always carry out self-development so that they always perform optimally in providing knowledge and being facilitators for students. The implications of teacher professional development relate to the quality of education. Professional development of teachers is very important to improve the quality of schools, the way teachers teach, and student achievement. Teachers participate in several types of professional development, including activities to improve knowledge, skills and attitudes. Practical learning is an activity that is closely related to teacher professionalism, carried out with the aim of getting the opportunity to test and apply theory using laboratory facilities/outside the laboratory. Practical learning is described as an activity that invites students' positive attitudes from the conditioning created by the teacher